Bifidobacterium obtained from mother's milk and their infant stool; A comparative genotyping and antibacterial analysis. (October 2017) - Eshaghi, Morteza; Bibalan, Meysam Hasannejad; Rohani, Mahdi; Esghaei, Maryam; Douraghi, Masoumeh; Talebi, Malihe; Pourshafie, Mohammad Reza
Abstract: Antibacterial activity of Bifidobacterium species has been considered as an important probiotic property for development of human gut immunity. This study was conducted to assess the genotypes and antibacterial activities of the native Bifidobacterium isolates obtained from the human's breast milk and the feces of their paired infants. Fifty-six samples from twenty-eight mothers' milk and paired infants feces were collected and cultured. Suspicious colonies were picked up and confirmed by phenotypic and molecular identifications. Randomly amplified polymorphic DNA (RAPD-PCR) and antibacterial activity were carried out. Amongst 56 samples, 41 different Bifidobacterium species including 12 B. breve, 14 B. longum, and 15 B. bifidum were isolated. Out of which, 12 isolates including B. longum (6), B. breve (4) and B. bifidum (2) were shared between six mother-infant pairs. Only three strains of B. longum showed 100% similarity in their RAPD-PCR. No significant difference was observed in the antibacterial activity of the Bifidobacterium isolates, with the same or different RAPD-PCR profile, against the enteric bacteria. Overall, 29% of the Bifidobacteria species isolated from the mothers milk and their paired infants feces were shared. All species of Bifidobacteria showed the universal role of antipathogens activities irrespective of the host and the isolation site. Highlights: Genotypic and phenotypic similarities amongst bifidobacterium strains isolated from human milk and paired breast-fed infants feces. The isolated bifidobacteria showed that about 29% of them were shared between mother-infant pairs. Out of the total isolates, only 50% of B. longum isolated from the breast milks and infant feces carried the same RPAD-PCR genotype. All bifidobacteria isolates showed antibacterial activities.